"y=-ln(dy\/dx)+xdy\/dx+1"
This is Clairaut equation
Differentiate both sides with respect to x
"{\\frac {dy} {dx}}=x{\\frac {d^2y} {dx^2}}+{\\frac {dy} {dx}}-{\\frac {{\\frac {d^2y} {dx^2}}} {{\\frac {dy} {dx}}}}"
Collect in terms of "{\\frac {d^2y} {dx^2}}"
"{\\frac {dy} {dx}}={\\frac {dy} {dx}}+{\\frac {d^2y} {dx^2}}(x-{\\frac {1} {{\\frac {dy} {dx}}}})"
Then
"{\\frac {d^2y} {dx^2}}(x-{\\frac {1} {{\\frac {dy} {dx}}}})=0"
Solve
"{\\frac {d^2y} {dx^2}}=0" and "(x-{\\frac {1} {{\\frac {dy} {dx}}}})=0" separately:
For "{\\frac {d^2y} {dx^2}}=0" :
"{\\frac {dy} {dx}}=\\int 0dx=C_1"
Substitute "y'=C_1" into initial equation
"y=-ln(C_1)+C_1x+1"
For "(x-{\\frac {1} {{\\frac {dy} {dx}}}})=0" :
"{\\frac {dy} {dx}}={\\frac {1} {x}}"
Substitute "y'=1\/x" into initial equation
"y=-ln({\\frac {1} {x}})+2"
Answer: "y=-ln(C_1)+C_1x+1" or "y=-ln({\\frac {1} {x}})+2"
Comments
Leave a comment